An amphiphilic PEG-b-PFPE-b-PEG triblock copolymer: synthesis by CuAAC click chemistry and self-assembly in water. Issue 2 (10th November 2015) - Lopez, Gérald; Guerre, Marc; Schmidt, Judith; Talmon, Yeshayahu; Ladmiral, Vincent; Habas, Jean-Pierre; Améduri, Bruno
Abstract : A new PEG2000 - b -PFPE1200 - b -PEG2000 amphiphilic triblock copolymer that undergoes self-assembly into micelles in water was synthesized by copper(i )-catalyzed alkyne–azide cycloaddition (CuAAC). Abstract : A new PEG2000 - b -PFPE1200 - b -PEG2000 amphiphilic triblock copolymer was synthesized by copper(i )-catalyzed alkyne–azide cycloaddition (CuAAC). The microstructure of this ABA triblock copolymer was unequivocally characterized by NMR spectroscopy. Diffusion-ordered spectroscopy (DOSY) NMR experiment revealed that 1 H resonances belonging to PEG and PFPE are aligned on the same horizontal line, thus implying that all these signals are due to the same macromolecule whose diffusion coefficient is lower than that of PEG and PFPE homopolymers. Thanks to its semi-fluorinated backbone bearing robust triazole rings, the PEG2000 - b -PFPE1200 - b -PEG2000 triblock copolymer exhibits good thermal stability with no significant weight loss until 275 °C under air. This triblock copolymer undergoes self-assembly into micelles ( D = 10–20 nm) in aqueous solution as confirmed from cryogenic-temperature transmission electron microscopy, DOSY experiment in D2 O, and dynamic light scattering. The critical micelle concentration was determined by pyrene fluorescence assay, and was found to be 0.1 mg mL −1 .